Changes in self-other boundaries modulate children’s body image attitudes - Cook, Caryn; Crucianelli, Laura; Filippetti, Maria Laura (Frontiers in Human Neuroscience, 2023)
One’s own face is a key distinctive feature of our physical appearance, yet multisensory visuo-tactile stimulation can alter self-other boundaries, eliciting changes in adult’s self-face representation and social cognition processes. This study tested whether changing self-face representation by altering self-other boundaries with the enfacement illusion modulates body image attitudes towards others in 6-to-11-year-old children (N = 51; 31 girls; predominantly White). Across all ages, congruent multisensory information led to stronger enfacement (η2p = 0.06). Participants who experienced a stronger enfacement illusion showed preference for larger body size, suggesting increased positive body size attitudes. This effect was stronger in 6–7-year-olds compared to 8–9-year-olds. Thus, blurring self-other boundaries successfully modulates self-face representation and body image attitudes towards others in children. Our results suggest that increased self-resemblance through self-other blurring resulting from the enfacement illusion may reduce social comparisons between self and other and result in positive body size attitudes.